Teachers' Personal and Collective Work-Identity Predicts Exhaustion and Work Motivation: Mediating Roles of Psychological Job Demands and Resources - Nordhall, Ola; Knez, Igor; Saboonchi, Fredrik; Willander, Johan (Frontiers in Psychology, 2020)
The aim of this study was to investigate the mediating roles of teacher’s psychological job demands and resources in relations between personal- and collective work-identity, respectively and exhaustion and self-determined work motivation, respectively. A total of 2905 members of a Swedish teacher’s trade union received a digitized questionnaire by e-mail where 768 individuals answered the questionnaire and by that participated in this study. The data were obtained by self-reported measures (e.g. emotional and cognitive components of work-identity, psychological job demands and resources, exhaustion and work motivation) and analyzed by mediation regression analyses. The results showed that teachers’ psychological job demands (prosocial extra role performance) mediated relationships between cognitive personal work-identity and emotional collective work-identity, respectively, and exhaustion. Teachers´ psychological job resources (educational inspiration) mediated relationships between emotional personal work-identity and cognitive collective work-identity, respectively, and self-determined work-motivation. Thus, teachers might be disadvantaged by stronger personal work-related thinking and collective work-related feeling when related to exhaustion, to some extent accounted for by psychological job demands, and they might find advantage in stronger personal work-related feeling and collective work-related thinking when related to work-motivation, to some extent accounted for by psychological job resources.